DIABETES MELLITUS AND SUDDEN DEATH: SOLVED AND UNSOLVED QUESTIONS - Немцова В. Д. (World of Medicine and Biology, 2015)
Diabetes mellitus is one of the most important medical and social problems in the world today. It is considered that the life expectancy of the patients with diabetes mellitus is 10 years less than those without metabolic disturbance and the leading cause of death are cardiovascular diseases, including sudden cardiac death which is about 50%, which was confirmed by numerous studies. However, till nowadays is not quite clear what is the cause of the increased risk of sudden death in these patients. This literature review devoted to the analysis of recent data on the possible causes of sudden death in patients with diabetes mellitus: a combination with coronary artery disease, left ventricular dysfunction, the role of hypoglycemia provoked arrhythmias, diabetic autonomic neuropathy development.It is known that in a population of the patients with myocardial infarction, diabetes mellitus increases the risk of sudden cardiac death. In addition, diabetes increases the risk of sudden cardiac death in patients with myocardial infarction and concomitant heart failure. Difficulty of coronary artery disease diagnosing in patients with diabetes is due to its frequent asymptomatic and atypical course. It is painless myocardial infarction is one of the causes of sudden death in patients with diabetes mellitus. The results of the Framingham study (2003) suggests that diabetes mellitus occurs the early development of left ventricular diastolic dysfunction, which leads to enlargement of left atrium, increasing the likelihood of arrhythmias. These data confirm the view that the relationship of diabetes and sudden cardiac death lies in the arrhythmogenic nature of diabetes. On the other hand, diabetes significantly increases the risk of cardiomyopathy with relevant mitochondrial dysfunction in pathogenesis, activation of fatty acid oxidation and other pathological processes whose activity depends on the activity of cellular metabolism and disorders of glucose metabolism associated with hypoglycemic episodes. However, nowadays despite the sufficient amount of investigations there is no conclusive evidence about the benefits of intensive glycemic control in order to reduce the incidence of cardiovascular events. Moreover, several studies have demonstrated the negative impact of strict control of glycemia on mortality. The is important to mark that not only lower blood glucose levels affects the occurrence of acute cardiac death, but hyperglycemia and a high daily blood glucose variation. Another predisposing factor for sudden cardiac death is diabetic cardiovascular autonomic neuropathy - pathological changes in the autonomic nervous system regulation of cardiac activity with a predominance of sympathetic influences and / or a decrease in vagal activity, which is observed in 22% of patients with type 2 diabetes and is considered a poor prognostic factor associated with increased incidence of sudden cardiac death.Summarizing accumulated till nowadays data, it is important to note that despite the fact that some risk factors for sudden death, such as microvascular pathology, autonomic neuropathy, expressed glycemic imbalance can be specific associated with diabetes in the recent recommendations of the European Society Cardiology and the European Association for the Study of Diabetes indicates that there is no conclusive data to create stratificational schemes and recommendations to prevent sudden cardiac death in diabetes. Therefore, greater emphasis should be placed on the proven risk factors for sudden cardiac death - the primary prevention of diabetes, atherosclerosis and coronary heart disease and secondary prevention of cardiovascular complications.
Keywords: diabetes mellitus; sudden death; risk factors